Mining Power Management - Rahmatov Baxtiyor (Proceedings of The ICECRS, 2019)
This paper makes analyses of the improving of the use of energy resources. As it is considered as one of the factors that contributes to the stability and sustainable development of the economy in all industries. Therefore, it has been investigated both theoritically and methodologically to make it as one of the most energy-intensive industries. To conclude with , qualitative changes in technology, the complication of mining and geological conditions for ore mining, and the introduction of environmental measures were mentioned as the whole.